The impact of internet use on air pollution: Evidence from emerging countries - Ozcan, Burcu; Apergis, Nicholas (Springer Heidelberg, 2018)
The goal of this study is to analyze the impact of Internet use, employed as a proxy for information and communications technologies (ICTs), on CO2 emissions. Using a panel of 20 emerging economies spanning the period 1990 to 2015, this paper finds that increased Internet access results in lower levels of air pollution. Moreover, panel causality test results highlight a unidirectional causality running from Internet use to CO2 emissions. This result also has crucial policy implications for the governments in emerging markets. For instance, increased investment in the ICT sector could be a plausible channel to reduce air pollution level.
Keywords: Air pollution; Emerging markets; Information and communications technologies; Internet use; Panel data